Overview of Bacterial Patterns and Antibiotic Sensitivity in Diabetic Foot Ulcers: A Single-Center Observational Study at Dr. M. Djamil General Hospital, Padang, Indonesia - Huda, Sri Nurul; Rismawati Yaswir; Syofiati (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Diabetic foot ulcers (DFUs) are a serious complication of diabetes mellitus with a high risk of infection. Patterns of causative bacteria and antibiotic sensitivity can vary between hospitals and time periods. Methods: This descriptive research involved all swabs and pus samples from DFU patients at Dr. M. Djamil General Hospital Padang between January and June 2023. Samples were processed through culture, Gram staining, and identification using VITEK 2. Patient medical record data was analyzed for demographic characteristics. Results: Of the 23 samples, 65% were gram-negative bacteria, dominated by Escherichia coli (30%). Gram-positive bacteria were found in 35%, with Staphylococcus aureus (18%) as the most. E. coli showed resistance to ampicillin and ceftriaxone but was sensitive to meropenem and amikacin. S. aureus is resistant to vancomycin but sensitive to benzylpenicillin. Conclusion: Gram-negative bacteria, especially E. coli, were more dominant in DFU at Dr. M. Djamil General Hospital Padang during the research period. The pattern of antibiotic resistance found emphasizes the importance of selecting appropriate antibiotic therapy based on sensitivity test results.